Functional Protective Coatings for Steel Architectural Construction Panels - Ryabova Anna V. (EDP Sciences, 2021)
Currently, enameled steel products are becoming very popular in construction, since they have a number of valuable properties that noticeably distinguish enameled architectural and construction panels against the background of other facing building materials. Also, extremely urgent is the problem of obtaining glass enamel coatings for architectural and construction panels with high properties. In the work, glass-crystalline enamel coatings in the system R2O–RO–B2O3–Al2O3–SiO2–TiO2–P2O2–F- were studied, the features of their formation on facing steel panels were revealed. The physicochemical and aesthetic-consumer properties of the developed enamel coatings have been investigated. The influence of the chemical composition of titanium-containing glass and the crystallization process on the whiteness index of white coating glass-crystalline enamels and the characteristic color shade was studied using a spectrophotometric method using an RGB color measurement model. This method made it possible to accurately determine the shades of the obtained glass-crystalline enamel coatings for steel.